Building Social Confiance With Dayah: Between Incidental Fanatism And Curricular Decision - Najmuddin, Najmuddin; Iqbal, Muhammad; Zahriyanti, Zahriyanti (AL-ISHLAH: Jurnal Pendidikan, 2024)
Dayah educational institutions have been popular in Aceh since the Sultanate of Iskandar Muda because of their ability to pass high-quality Muslim scholars. This is due to his ability to apply the fanatic attitude of the leadership to the quality of the curriculum in Aceh. Despite the many emerging modern teaching approaches in advancing formal educational institutions, Fanaticism in this context has provided high enthusiasm for students and the community in studying Islamic religious knowledge within the scope of the Acehnese Salafi Dayah. Therefore, this study aims to discuss the forces of fanaticism led by dayah and investigate the effectiveness of the quality of the dayah curriculum in Aceh. This research is classied as qualitative descriptive. Data collection was carried out through observation, interviews, and documentation. Data is obtained from interviews with Dayah Leaders, Wadir, and teachers at Dayah MUDI Bireuen, Aceh, observing the implementation of fanaticism-based learning and reviewing supporting documents. The analysis is data reduction, data presentation, and conclusion. The results of this research reveal that, First, fanaticism in learning in the Dayah has inherited the charismatic Muslim scientists/Ulama in Aceh. Second, the collaboration between passionate leadership in the Dayah and the quality of the curriculum has helped develop the students' competence. Third, the support of Dayah teachers and Dayah alumni rabithah has increased public trust.